Penyuluhan media audio terhadap pengetahuan dan tingkat kebersihan gigi dan mulut - Femala, Dian; Ayatullah, M. Ibraar (Journal of Oral Health Care, 2020)
Abstract: Audio Media Outreach to Knowledge and Levels of Dental and Oral Hygiene . Primary school is a very strategic place for the prevention of dental and oral diseases. Delivering counseling material in learning oral health requires a media. The media in dental and oral health education is one of them by counseling using audio media. This audio media contains messages about dental health that are played at school every morning and can be exposed and heard every day so that elementary school children behave well in dental health. This study aims to determine the effectiveness of audio media outreach to the knowledge and level of dental and mouth hygiene of students at SDN 26 Kalimas Tengah Kubu Raya Regency in 2019. This study was a quasi-experimental study with a Pre-Post observation research design. The samples of this study were 68 people, namely class III, IV and V. The results showed the average rank of knowledge index before counseling with audio media was 8.928 and p was 0.020 (p <0.05) with index of dental and oral hygiene level was 0 , 00 and p of 0,000 (p <0.05) while after counseling with audio media was 9,500 and p of 0.020 (p <0.05) with a level of dental and oral hygiene of 35.00 and p of 0,000 (p <0 , 05). The conclusion of this research is that counseling with audio media is more effective in increasing knowledge can improve oral and dental hygiene. Abstrak: Penyuluhan Media Audio terhadap Pengetahuan dan Tingkat Kebersihan Gigi dan Mulut. Sekolah dasar merupakantempat yang sangat strategis untuk penanggulangan penyakit gigi dan mulut. Penyampaikan materi penyuluhan dalam pembelajaran kesehatan gigi dan mulut ini dibutuhkan suatu media.Media dalam pendidikan kesehan gigi dan mulut salah satunya dengan penyuluhan menggunakan media audio.Media audio ini berisikan pesan tentang kesehatan gigi yang diputar disekolah setiap pagi dan bisa terpapar dan di dengar setiap hari sehingga anak sekolah dasar berperilaku baik dalam kesehatan gigi. Penelitian ini bertujuan untuk mengetahui efektifitas penyuluhan media audio terhadap pengetahuan dan tingkat kebersihan gigi dan mulut murid SDN 26 Kalimas Tengah Kabupaten Kubu Raya Tahun 2019. Penelitian ini adalah penelitian eksperimental semu dengan rancangan penelitian Pre-Post observasi. Sampel penelitian ini sebanyak 68 Orang yaitu kelas III, IV dan V.Hasil penelitian menunjukkan rata-rata rank indeks pengetahuan sebelum penyuluhan dengan media audio adalah 8,928 dan p sebesar 0,020 (p<0,05) dengan indeks tingkat kebersihan gigi dan mulut adalah 0,00 dan p sebesar 0,000 (p<0,05) sedangkan sesudah penyuluhan dengan media audio adalah 9,500 dan p sebesar 0,020 (p<0,05) dengan tingkat kebersihan gigi dan mulut adalah 35,00 dan p-value sebesar 0,000 (p<0,05). Simpulan penelitian ini bahwa penyuluhan dengan media audio lebih efektif dalam meningkatkan pengetahuan dapat meningkatkan kebersihan gigi dan mulut.